Réponses

2014-09-07T14:32:02+02:00
A) (+9) - (+12)
On change le - en +, donc le +12 deviens -12
(+9) + (-12)
= -3

B) (-10) - (+6)
Même chose
(-10) + ( -6 )
= -16
C) (-2) - (-17)
(-2) + (+17)
= +15

D) (-13) - (-5)
(-13) + (+5)
= -8

E) (+8) - (-1)
(+8) + (+1)
= 9

F) 0 - (-72)
0 + (+72)
= 72

Si tu as des questions.. ^^
Meilleure réponse !
  • Utilisateur Brainly
2014-09-07T15:31:39+02:00
(+ 9) - (+ 12)
= 9 - 12
= - 3

(- 10) - (+ 6)
= - 10 - 6
= - 16

(- 2) - (- 17)
= - 2 + 17
= -15

(- 13) - (- 5)
= - 13 + 5
= - 8

(+ 8) - (- 1)
= 8 + 1
= 9

0 - (- 72)
= 0 + 72
= 72